The relationship between organizational culture and employees' job performance at Pejabat Pendidikan Daerah (PPD) Pasir Puteh / Nur Hidayah Abu Johan - Abu Johan, Nur Hidayah (Faculty of Business and Management, 2018)
This research has been concluded to identify relationship between organizational culture and employees' job performance at Pejabat Pendidikan Oaerah (PPD) Pasir Puteh. This research has four research questions which are the level of overall organizational culture, organizational culture traits has the highest level of implementation among employees, the level of overall job performances of employees and the relationship between organizational culture and employees' job performance. The scopes of this research are focused on 60 number of population. The sample sizes taken are 54 respondents as referred to the sample size for a given population by Krejcie and Morgan (1970). The sampling technique used is simple· random sampling. The research findings can be concluded that there is positive relationship between four traits of organizational culture and employees' job performance at Pejabat Pendidikan Oaerah (PPO) Pasir Puteh.